2008
DOI: 10.1097/mpg.0b013e3181615cba
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein and Energy Intakes on Body Composition of Formula‐fed Preterm Infants After Term

Abstract: The aim of the present study was to evaluate changes in body composition in 48 preterm infants in relation to protein and energy intakes from term up to 3 months of corrected age, using air displacement plethysmography. Protein intake (grams per kilogram per day) was negatively associated with percentage of fat mass at 1 month of corrected age. The high-protein-intake group showed greater gain in lean body mass gain than did the low-protein-intake group. This finding suggests that during the first month of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
4
29
0
3
Order By: Relevance
“…Our study provides support for previous research indicating that preterm infants near or at term-corrected age have a higher percent body fat than infants born term (5)(6)(7)(8). Furthermore, our findings indicate that anthropometry, skinfolds, and ADP are efficient to detect significant differences in body composition between preterm and term infants at hospital discharge.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study provides support for previous research indicating that preterm infants near or at term-corrected age have a higher percent body fat than infants born term (5)(6)(7)(8). Furthermore, our findings indicate that anthropometry, skinfolds, and ADP are efficient to detect significant differences in body composition between preterm and term infants at hospital discharge.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, the lack of correlation between preterm infant caloric intake and body fat is consistent with other research studies (5,15). However, unlike this study, other studies have shown a relationship between protein intake and lean mass (6,16). Overall, the current study results on gender, salivary cortisol levels, and dietary intake need to be interpreted with caution due to the small sample size.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The latter finding is somewhat surprising because a higher delta fat mass in SGA late preterm infants could have been expected, higher than that in the AGA late preterm infants because SGA very preterm infants have demonstrated rapid postnatal catch-up with respect to fat (12). However, it can be speculated that because protein intake has been reported to be associated with a significantly different weight gain composition (13,14), the lack of higher fat mass accretion in SGA late preterm infants could be because they actually received similar protein and energy intake compared to AGA late preterm infants.Based on the present results, late preterm infants gain more fat mass than what they would have gained if they had remained in utero, a finding that is in agreement with previous studies. De Marini et al (9).…”
mentioning
confidence: 94%
“…In a non-randomised study, Roggero et al 26 , used whole-body plethysmography to measure weight gain and LBM accural at 1 month post-term age in preterm infants fed either a high-protein diet (> 3 g/kg/day) (n = 26) or a low-protein diet (< 3 g/kg/day) (n = 22). Weight gain was significantly lower in the high-protein group than in the low-protein group {mean [standard deviation (SD) …”
mentioning
confidence: 99%